1999
DOI: 10.1080/09712119.1999.9706258
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Acetogenesis in the Hindgut and Attempts to its Induction in the Rumen—A Review

Abstract: Fievez, V., Piattoni, F., Mbanzamihigo, L. and Demeyer, D. 1999. Reductive acetogenesis in the hindgut and attempts to its induction in the rumen-A review. J. Appl. Anim. Res., 16: 1-22. Hiridgut ferrneiitatiori differs froin ruinen fermentation b. y a. lower methane production and the presence of reductive acetogenesis (RA).Moreover, it has been showii tha.t with ageing RA is rephced coinpletely (ruinen) or partially (hindgut) A. IntroductionBesides methanogenesis (M), non assimilatory sulphate reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
1
18
0
1
Order By: Relevance
“…However, there was a clear host-specific effect on the gut acetogen community in the host animals used in our study. The higher richness (the number of different species present) and evenness (the frequencies of the different units making up a population) of acetogen populations in horse and rabbit compared to ruminants suggested that the monogastric herbivores own a more diverse acetogen community than ruminants, which is consistent consistent with previous reports that reductive acetogenesis is a more important hydrogen disposal method in the hindgut when compared to the rumen [24,30]. In addition, cows and sheep, as ruminants, showed a rather different acetogen community when compared to rabbits and horses, characterized by phylogenetically different distributed ACS OTUs.…”
Section: Discussionsupporting
confidence: 82%
“…However, there was a clear host-specific effect on the gut acetogen community in the host animals used in our study. The higher richness (the number of different species present) and evenness (the frequencies of the different units making up a population) of acetogen populations in horse and rabbit compared to ruminants suggested that the monogastric herbivores own a more diverse acetogen community than ruminants, which is consistent consistent with previous reports that reductive acetogenesis is a more important hydrogen disposal method in the hindgut when compared to the rumen [24,30]. In addition, cows and sheep, as ruminants, showed a rather different acetogen community when compared to rabbits and horses, characterized by phylogenetically different distributed ACS OTUs.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, tannins decrease the degradation of nutrients in the rumen which then may be degraded in the hindgut. This could have contributed to a lower methane emission, too, because hindgut fermentation differs from ruminal fermentation by resulting in a lower methane production per unit of fermented nutrients [6]. The results of the present experiments confirm previous assumptions that extracted tannins [2] as well as tannin-rich legumes can be useful in limiting methane emissions but, when employing tannins in the form of very tannin-rich legumes, a simultaneous depression of the feeding value of the diet may question the viability of this feeding measure.…”
Section: Resultsmentioning
confidence: 97%
“…envers des produits animaux, les antibiotiques) empê-chent une application pratique. Les interventions biotechnologiques sont difficiles à appliquer en pratique (défaunation) [18] ou restent toujours très spéculatives (acéto-genèse réductrice) [22].…”
Section: Chunclassified